Perancangan Aplikasi Pembayaran SPP dan Penggajian Guru Berbasis Web Pada Bimbingan Belajar - Abadi, Reagent; Wasino, Wasino; Lina, Lina (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The Web-Based SPP Payment and Teacher Payroll Application for tutoring centers is designed to enhance efficiency in financial management, specifically in recording student SPP payments and teacher payroll processing. Previously, financial management processes were manual, making them prone to errors and time-consuming. This application automates data recording and provides a more structured data storage, reducing the risk of common errors in manual systems. The System Development Life Cycle (SDLC) with the Waterfall methodology was adopted in developing this application, following structured and systematic stages. The application involves five main actors—Admin, Owner, Teacher, Student, and Visitor—each having tailored access to relevant features. Technically, the application is built using HTML, JavaScript, CSS, jQuery, and PHP, supported by the Bootstrap framework for a responsive interface, while MySQL is used as the database to store data. The objective is to enable more effective, accurate, and efficient SPP payment recording and teacher payroll processing while minimizing human errors due to oversight..